HOBO Water Temperature Pro Data Logger observations at East Snake Caye, Belize, between June 2002 and November 2007 - Georgios Margaritis; Karl D Castillo (PANGAEA, 2025)
HOBO Water Temperature Pro Data Loggers (accuracy ± 0.2 °C and resolution 0.02 °C; http://www.onsetcomp.com) were installed at East Snake Caye within the inner lagoon reef and White Reef on the outer barrier reef. They recorded temperatures at 15-minute intervals from June 2002 to August 2005 and 10-minute intervals from October 2006 to December 2007. The logger observations, made at 3-6m depth were used as an in situ reference, to validate two satellite SST products (NOAA extquotesingles CoralTemp and ESA CCI extquotesingles SST version 2.1) used in coral reef monitoring. A full description of the installation process is available in Castillo KD, Lima FP. Comparison of in situ and satellite-derived (MODIS-Aqua/Terra) methods for assessing temperatures on coral reefs. Limnology and Oceanography: Methods. 2010;8(3):107-17.